1979
DOI: 10.1159/000272439
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Personal Possessions: Explanations for and Judgments about Unequal Distribution

Abstract: This study examines concepts about and evaluations of the unequal distribution of personal possessions. As an exploratory study, its purpose was to map the dimensions of (a) explanations for the existence of unequal distribution and (b) judgments or evaluations of inequality. Interview questions were administered to (a) 150 Americans, 30 at each of five age levels (kindergarten, second, fifth, and eleventh grades, and 40- to 50-year-old adults), and to (b) 120 Israelis, 60 from the kibbutz and 60 from the city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
(20 reference statements)
2
16
0
2
Order By: Relevance
“…1978;King et al, 1983;Langford, 1975;Murphy and Gilligan, 1980;Perry, 1970;Sinnott, 1983] or indirectly [Arlin, 1975, andHartley, 1980, on problem finding; Commons et al, 1982, on metasystematic operations;Powell. 1980, on category operations;and Furby, 1979, on rea soning about unequal distribution]. Some of these studies have found increasing inci dences of relativistic and/or dialectical thought with entrance into early adulthood, both longitudinally [King et al, 1983] and cross-sectionally [Basseches, 1980;Com mons et al, 1982;Furby, 1979;Olsen et al, 1982] or with entrance into middle-age [Bas seches, 1980], Others have found no such dif ferences [Hartley, 1980;Powell, 1980;Sin nott, 1983].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1978;King et al, 1983;Langford, 1975;Murphy and Gilligan, 1980;Perry, 1970;Sinnott, 1983] or indirectly [Arlin, 1975, andHartley, 1980, on problem finding; Commons et al, 1982, on metasystematic operations;Powell. 1980, on category operations;and Furby, 1979, on rea soning about unequal distribution]. Some of these studies have found increasing inci dences of relativistic and/or dialectical thought with entrance into early adulthood, both longitudinally [King et al, 1983] and cross-sectionally [Basseches, 1980;Com mons et al, 1982;Furby, 1979;Olsen et al, 1982] or with entrance into middle-age [Bas seches, 1980], Others have found no such dif ferences [Hartley, 1980;Powell, 1980;Sin nott, 1983].…”
mentioning
confidence: 99%
“…1980, on category operations;and Furby, 1979, on rea soning about unequal distribution]. Some of these studies have found increasing inci dences of relativistic and/or dialectical thought with entrance into early adulthood, both longitudinally [King et al, 1983] and cross-sectionally [Basseches, 1980;Com mons et al, 1982;Furby, 1979;Olsen et al, 1982] or with entrance into middle-age [Bas seches, 1980], Others have found no such dif ferences [Hartley, 1980;Powell, 1980;Sin nott, 1983]. Still others provided no numer ical or statistical data by which to make an adequate judgement regarding possible age differences [Broughton, 1978;Furby, 1979;Langford, 1975;Perry, 1970;Murphy and Gilligan, 1980], although age-related progres sions were reported for a number of these studies [Broughton, 1978;Perry, 1970;Mur phy and Gilligan, 1980].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their mum and dad don't have much money' (Child # 40). A number of studies conducted in the previous century have also found that by the age of six, children develop some awareness about social and economic issues related to people who live in foreign countries (Barrett & Short, 1992;Furby, 1979;Jahoda, 1962;Lambert & Klineberg, 1967;Piaget & Weil, 1951). However, a few (5.7%) of the children stated that they did not know whether all children could afford to buy new toys from a shop or not.…”
Section: Children's Knowledge and Views Of Economic (In)equalities Inmentioning
confidence: 99%
“…A number of studies that were conducted in the previous century have shown that by the age of six, children develop a level of awareness regarding the social and economic issues related to other people, who belong to various national groups, and they also acquire some knowledge of and belief about foreign countries and people (Barrett & Short, 1992;Furby, 1979;Jahoda, 1962;Lambert & Klineberg, 1967;Piaget & Weil, 1951). However, no recent studies were identified that investigated preschool children's knowledge or views of the lives, well-being and economic conditions of children who live in other countries.…”
Section: Introductionmentioning
confidence: 99%